The undomesticated Rock Dove in Britain and the Isle of Man - Smith, W (BB 2000, 2023)
The domestic pigeon Columba livia has a close relationship with humans, both in captivity and in a feral state, the Feral Pigeon. The domestic pigeon’s ancestor, the wild Rock Dove, is, however, something of an enigma: following extensive hybridisation with Feral Pigeons across its range (with many populations of Rock Doves becoming extinct by hybridisation with Feral Pigeons), little is known of its contemporary distribution, nor of the genetic purity of the remaining populat- ions. Putative populations of wild Rock Doves have long been known to inhabit coastal regions of Britain and the Isle of Man but they have been subject to little research. This paper outlines the existing knowledge regarding the distribution and genetic status of Rock Doves in Britain and the Isle of Man, and assesses the likely impact of ongoing hybridisation on the continued persistence of the Rock Dove.